Association between neighbourhood deprivation and hypertension in a US-wide Cohort. Issue 3 (17th November 2021) - Xu, Jing; Lawrence, Kaitlyn G; O'Brien, Katie M; Jackson, Chandra L; Sandler, Dale P
Abstract : Background: Socioeconomic status (SES) at the individual level is associated with hypertension risk. Less is known about neighbourhood level SES or how neighbourhood and individual level SES may jointly affect hypertension risk. Methods: The Area Deprivation Index (ADI) includes 17 census-based measures reflecting neighbourhood SES. The ADI was linked to enrolment addresses of 47 329 women in the Sister Study cohort and categorised as ≤10% (low deprivation), 11%–20%, 21%–35%, 36%–55% and >55% (high deprivation). Hypertension was defined as either high systolic (≥140 mm Hg) or diastolic (≥90 mm Hg) blood pressure or taking antihypertensive medication. We used log binomial regression to investigate the cross-sectional association between ADI and hypertension and evaluated interactions between ADI and race/ethnicity and between ADI and individual SES. Results: The highest ADI level of >55% was associated with increased prevalence of hypertension, compared with the lowest level of ADI≤10%, in a model adjusted for age, race/ethnicity, educational attainment and annual household income (prevalence ratio=1.26, 95% CI 1.21 to 1.32). We observed interaction between race/ethnicity and ADI (interaction contrast ratio (ICR)=1.9; 95% CI 0.94 to 2.8 comparing non-Hispanic Black women with ADI >55% to non-Hispanic White women with ADI≤10%) and between household income and ADI (ICR 0.38; 95% CI 0.12 to 0.65 comparing participants with household income ≤US$49 999 and ADI>55% to those with household income >US$100 000 and ADI≤10%). Conclusions: These findings suggest that neighbourhood deprivation measured by ADI may be a risk factor for hypertension and that ADI may act synergistically with race/ethnicity and individual household income to contribute to hypertension.